Hepatosplenic candidiasis with generalized cutaneous nodular lesions: a case report - (:unkn) unknown (My University, 2013)
Kronik yaygın (dissemine) kandidiyazis olarak da bilinen hepatosplenik kandidiyazis (HSC) karaciğer, dalak ve böbreği tutan invazif mantar enfeksiyonudur. Çocukluk çağı kanserlerinde uygulanan kemoterapi sonrası nötro- peni gelişen hastalarda, giderek artan sıklıkta tespit edilmektedir. Kesin tanı kan ve doku kültürlerinde pato- jenin üretilmesi veya biyopsi örneklerinde etkenin göste- rilmesi ile konur. Temel tedavi yaklaşımı parenteral amfoterisin B uygulamasıdır. Bu yazıda; evre 4 nörob- lastom tanısı ile kemoterapi almakta iken, febril nötrope- ni atağı esnasında gelişen hepatosplenik kandidiyazis nedeniyle sırtında ve kollarında çok sayıda nodüler lez- yonlar gözlenen 7 yaşında bir olgu sunulmuştur. Radyolojik tetkikler ve kan kültürü ile HSC tanısı alan ancak amfoterisin B tedavisine yanıt vermeyen hasta, uzun süre uygulanan kaspofungin ile tedavi edilebilmiş- tir. (J Pediatr Inf 2013; 7: 39-42)

Hepatosplenic candidiasis (HSC), also commonly known as chronic disseminated candidiasis, is a distinct form of disseminated Candida supp. infection, with predominant involvement of the liver, spleen and occa- sionally the kidneys. It is detected with increasing fre- quency in patients who developed neutropenia after chemotherapy in childhood cancers. A definitive diag- nosis is made by producing the pathogen in culture or showing the pathogen in biopsy specimens. The basic approach in treatment is the use of parenteral amphoth- ericine B. In this paper, a case of a 7 year old patient who developed a large number of nodular lesions on his back and arms in febrile neutropenic episodes while receiving chemotherapy with a diagnosis of stage 4 neuroblastoma is presented. The patient, who was diagnosed with the HSC after radiological tests and blood cultures but did not respond to treatment with amphotericin B, was only treated with caspofungin for a long time. (J Pediatr Inf 2013; 7: 39-42)
Ciltte yaygın nodüler lezyonlarla birliktelik gösteren hepatosplenik kandidiyazis: olgu sunumu
Keywords: Hematoloji; Pediatri